2013
DOI: 10.1186/1475-2875-12-360
|View full text |Cite
|
Sign up to set email alerts
|

Towards improved uptake of malaria chemoprophylaxis among West African travellers: identification of behavioural determinants

Abstract: BackgroundMalaria is a potentially lethal illness for which preventive measures are not optimally used among all travellers. Travellers visiting friends and relatives in their country of origin (VFRs) are known to use chemoprophylaxis less consistently compared to tourist travellers. In this study, factors explaining the low use of chemoprophylaxis were pursued to contribute to improving uptake of preventive measures among VFRs.MethodsFollowing in-depth interviews with Ghanaians living in Amsterdam, a question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 20 publications
2
34
0
Order By: Relevance
“…Challenges in adherence are not limited to the concept of SBET but are also seen for continuous malaria chemoprophylaxis for travellers to high-risk countries [2226]. Several studies prove that the majority of returning travellers with malaria did not take malaria chemoprophylaxis or applied an incorrect regimen, the majority being travellers visiting friends or relatives (VFR) abroad [22, 2731]. …”
Section: Discussionmentioning
confidence: 99%
“…Challenges in adherence are not limited to the concept of SBET but are also seen for continuous malaria chemoprophylaxis for travellers to high-risk countries [2226]. Several studies prove that the majority of returning travellers with malaria did not take malaria chemoprophylaxis or applied an incorrect regimen, the majority being travellers visiting friends or relatives (VFR) abroad [22, 2731]. …”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed in our study, as VFR travellers account for a significant fraction of our study population (48.6%). VFR travellers may mistakenly believe that previous, partial immunity protects them from the disease [31] which is true with regard to protection against severe disease [32]. The cost of the chemoprophylaxis is also believed to be a discouraging factor for some VFRs [33].…”
Section: Discussionmentioning
confidence: 99%
“…Eleven studies found that older participants were more likely to be adherent [12,17,18,20,21,24,30,32,[38][39][40]. Another study reported that those under 30 were less likely to be adherent than older people [22], but significance was not reported.…”
Section: Demographic Risk Factorsmentioning
confidence: 99%
“…Wieten et al [38] Travellers to Ghana from the Netherlands 154 Questionnaire survey 53.9% (had started chemoprophylaxis) Attending pretravel clinic and receiving pre-travel advice was related to a greater likelihood of starting chemoprophylaxis (p < 0.01); if a participant incorrectly thought they had been vaccinated (p = 0.009) they were also more likely to use chemoprophylaxis Higher age (p = 0.004) and travelling for family purposes (p = 0.022) rather than business were positively associated with starting chemoprophylaxis. Having had malaria (p = 0.028) and spending more than 6 weeks in West Africa (p = 0.001) were negatively associated with starting and buying chemoprophylaxis Those who thought curing malaria was easier than taking preventative tablets (p = 0.046) were more likely to be nonadherent-it was felt that subjectively held information is more important than accurate information Previous use of chemoprophylaxis was not found to influence current preventive behaviour Medium to be non-adherent compared with white-collar workers [41].…”
Section: Mediummentioning
confidence: 99%